Pengambilan Keputusan Etis dalam Novel Burlian Karya Tere Liye: Kajian Literasi Moral - Idris, Akhmad (citeus, 2019)
This research is motivated by three things, namely 1) moral literacy which becomes an ability that needs to be considered in the 21st century, 2) moral literacy which is used to make ethical decisions, and 3) Burlian novel which is one of the literary works that reflects moral literacy. This study aims to describe the ethical decision making in the novel Burlian by Tere Liye with the study of moral literacy. This research is a qualitative descriptive type. Data collection were taken through library techniques and data analysis techniques using content analysis techniques. The results of this study indicate that ethical decision making is based on three components of moral literacy, namely ethical sensitivity, ethical reasoning, and moral imagination. The pattern of the three components of moral literacy is ethical sensitivity as a form of ethical action, whereas ethical reasoning and moral imagination are the foundation of the ethical action.